2013
DOI: 10.1007/s00464-012-2772-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic adrenalectomy for malignant lesions: surgical principles to improve oncologic outcomes

Abstract: LA for primary or metastatic malignant lesions is feasible and seems oncologically safe. Surgical principles should be the same for all LA: en bloc resection of all epinephric fat, minimal touch technique, and low threshold for conversion. Size of the lesion alone should not be an indication for open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
1
13
0
2
Order By: Relevance
“…The authors claim that the key element in surgery for any malignancy is not the surgical access itself but the proper technique. Similar results were shown by Sroka et al [27]. He concluded that the size of the lesion alone should not be an indication for open surgery and laparoscopy for adrenal malignancy is safe when basic oncological principles are applied.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The authors claim that the key element in surgery for any malignancy is not the surgical access itself but the proper technique. Similar results were shown by Sroka et al [27]. He concluded that the size of the lesion alone should not be an indication for open surgery and laparoscopy for adrenal malignancy is safe when basic oncological principles are applied.…”
Section: Discussionsupporting
confidence: 76%
“…In our series of tumors >6 cm, we found only 4 (4.5%) cases of ACC. Similarly, such low incidence can be found elsewhere [27]. Close adherence to the principle of using only open approach in case of tumors >6 cm would deprive 95% of patients the benefits of laparoscopic operation exposing them unnecessarily to higher complication rate, slower recovery, more postoperative pain and other disadvantages of open surgery [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Our own data from Germany support this view. (16,17,18,19,20,21,22,23,24), but there is no conclusive answer to date. As to the other two questions, the available literature is even scarcer (9,25,26,27).…”
Section: Surgerymentioning
confidence: 99%
“…Кроме того, в ряде исследований была доказана также возможность успешного применения эндоскопического доступа для выполнения операций по поводу неоплазий, в своем максимальном измерении значительно пре-вышающих вышеозначенное условное пороговое значение [5][6][7][8][9]. Некоторыми авторами получены обнадеживающие результаты у пациентов с малиг-низированными опухолями адреналовых желез при проведении лапароскопических адреналэктомий (ЛАЭ) на ранних стадиях злокачественного процес-са [10][11][12]. В целом проведенные исследования четко про-демонстрировали преимущества эндохирургическо-го доступа над традиционным открытым при вы-полнении АЭ.…”
unclassified